2011
DOI: 10.1007/s00468-011-0594-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved organogenic capacity of shoot cultures from mature pedunculate oak trees through somatic embryogenesis as rejuvenation technique

Abstract: Theoretically, complete rejuvenation of mature trees should occur through somatic embryogenesis, however, this has not been extensively studied. The main objective of the present study was to increase the efficiency of in vitro clonal propagation for mature Quercus robur (100-300 years old), by induction of somatic embryogenesis as rejuvenation step prior to establishment of shoot culture through micropropagation of somatic embryo-derived plantlets. Shoot culture lines of ''mature'' origin were established fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…As human management of the dehesas usually involves removal of the shrub layer and clearance of the arboreal stratum (Mesías et al 2010), holm oak trees do not usually have basal shoots. In the absence of mature material with juvenile physiological characteristics, an alternative procedure based on forced flushing of branch segments can be used to produce epicormic shoots, which are a source of more reactive and reinvigorated explants (Martínez et al 2012). In the present study, this method enabled the establishment and proliferation of shoot cultures from material derived from the crowns of mature trees.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As human management of the dehesas usually involves removal of the shrub layer and clearance of the arboreal stratum (Mesías et al 2010), holm oak trees do not usually have basal shoots. In the absence of mature material with juvenile physiological characteristics, an alternative procedure based on forced flushing of branch segments can be used to produce epicormic shoots, which are a source of more reactive and reinvigorated explants (Martínez et al 2012). In the present study, this method enabled the establishment and proliferation of shoot cultures from material derived from the crowns of mature trees.…”
Section: Discussionmentioning
confidence: 93%
“…Although little is known about the rooting of axillary shoot cultures established from crown material obtained from woody plants, in general the rooting rates are lower than yielded by basal shoots. Martínez et al (2012) reported that shoot cultures derived from the crown of a Q. robur tree displayed a low rooting capacity (3.3%), whereas shoot cultures collected from the same mature tree, but derived from basal sprouts, displayed a much higher rooting capacity (71.5%). Similar results have been reported for chestnut (Sánchez and Vieitez 1991) and Sequoia sempervirens (Bon et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, further molecular analysis as well as a study of true-to-type phenotype of regenerated plants would be recommended, especially if embryogenic callus were kept for a long time in culture. In any case, taking into account that commercial olive micropropagation shows a strong genotype effect (Zuccherelli and Zuccherelli, 2002), regeneration and genetic fidelity of adult plants derived from somatic embryos open new opportunities to propagate recalcitrant cultivars, i.e., obtained material could be used as revitalized mother plants and further multiplied either in vitro , through nodal segmentation of elongated shoots, or in vivo , by rooted minicuttings, as reported in other woody species (Martínez et al, 2012; Georget et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic embryogenesis can cause rejuvenation in mature Quercus robur [6]. Huang et al reported that, after five instances of repeated grafting of adult shoot tips onto juvenile rootstock in vitro, a rejuvenation phenomenon occurred in S. sempervirens [4].…”
Section: Introductionmentioning
confidence: 99%